The Signaling Molecule Indole Inhibits Induction of the AR2 Acid Resistance System in Escherichia coli - Boon, Nathaniel; Kaur, Manpreet; Aziz, Amina; Bradnick, Morissa; Shibayama, Kenta; Eguchi, Yoko; Lund, Peter A. (Frontiers in Microbiology, 2020)
Induction of the AR2 acid response system of Escherichia coli by a moderately low pH (pH 5.5) is mediated in part by the EvgAS two component system. Here, we show that the action of the EvgS sensor kinase is inhibited by micromolar concentrations of the bacterial signalling molecule indole. Indole prevented the EvgAS-mediated induction of promoters for genes from the AR2 system, and also prevented the development of acid tolerance following exposure of cells to a mild acid shock of pH 5.5. Induction of EvgAS-activated promoters and development of acid tolerance was also blocked by the addition of tryptophan, the precursor for indole biosynthesis. This block was relieved in a tnaA mutant that is unable to synthesise indole. A constitutively active EvgS mutant was not inhibited by indole, and indole also had no effect on autophosphorylation of the isolated cytoplasmic domain of EvgS. This suggests that indole directly or indirectly affects the ability of EvgS to detect its inducing signal or to transduce this information across the cytoplasmic membrane. The inhibitory activity of indole on EvgS is not related to its ability to act as an ionophore, and the ionophore CCCP had no effect on EvgS-mediated promoter activity, showing that EvgS is unlikely to be affected by the proton motive force.